Effect of Ultrasound‐Stimulated Microbubbles and Hyperthermia on Tumor Vasculature of Breast Cancer Xenograft. (10th February 2022) - Sharma, Deepa; Cartar, Holliday; Quiaoit, Karina; Law, Niki; Giles, Anoja; Czarnota, Gregory J.
Abstract : Objective: The objective of the present study was to investigate the treatment effects of ultrasound‐stimulated microbubbles (USMB) and hyperthermia (HT) on breast tumor vasculature. Methods: Tumor‐bearing mice with breast cancer xenografts (MDA‐MB‐231), were exposed to different treatment conditions consisting of control (no treatment), USMB alone, HT alone, USMB with HT exposures of 10 and 50 minutes. Quantitative 3D Doppler ultrasound and photoacoustic imaging were used to detect tumor blood flow and oxygen saturation, respectively. In addition, histopathological analysis including TUNEL staining for cell death, and CD31 staining for the vessel count, was performed to complement the results of power Doppler and photoacoustic imaging. Results: Results demonstrated a decrease in tumor blood flow as well as oxygenation level following 50 minutes HT treatment either alone or combined with USMB. In contrast, 10 minutes HT alone or combined with USMB had minimal effects on blood flow and tumor oxygenation level. Treatment with HT for 50 minutes caused drops in tumor oxygenation, which were not evident with USMB treatment alone. Additionally, results revealed an increase in cell death after 10 minutes HT with or without USMB and a decrease in vessel count compared to control. Unlike previous studies which demonstrated synergistic treatment effects combining USMB with other modalities such as radiation or chemotherapy, USMB and HT effects were not synergistic in the present study. Conclusion: The results here demonstrated HT and USMB both alone or together resulted in a significant reduction in tumor blood flow, tumor oxygenation, and vessel count with observed increases in cell death response.